Electron and donor-impurity-related Raman scattering and Raman gain in triangular quantum dots under an applied electric field (2016)
ABSTRACT: The differential cross-section of electron Raman scattering and the Raman gain are calculated and analysed in the case of prismatic quantum dots with equilateral triangle base shape. The study takes into account their dependencies on the size of the triangle, the influence of externally applied electric field as well as the presence of an ionized donor center located at the triangle’s orthocenter. The calculations are made within the effective mass and parabolic band approximations, with a diagonalization scheme being applied to obtain the eigenfunctions and eigenvalues of the x-y Hamiltonian. The incident and secondary (scattered) radiation have been considered linearly-polarized along the y-direction, coinciding with the direction of the applied electric field. For the case with an impurity center, Raman scattering with the intermediate state energy below the initial state one has been found to show maximum differential cross-section more than by an order of magnitude bigger than that resulting from the scheme with lower intermediate state energy. The Raman gain has maximum magnitude around 35 nm dot size and electric field of 40 kV/cm for the case without impurity and at maximum considered values of the input parameters for the case with impurity. Values of Raman gain of the order of up to 104 cm−1 are predicted in both cases.